1991
DOI: 10.1021/es00021a013
|View full text |Cite
|
Sign up to set email alerts
|

Role of dissolved oxygen on the adsorptive capacity of activated carbon for synthetic and natural organic matter

Abstract: Parameters affecting the adsorptive capacity of granular activated carbon (GAC) for o-cresol, phenol, o-chlorophenol, 3-ethylphenol, trichloroethylene, and natural organic matter are investigated in this study. Experimental results prove that the presence of molecular oxygen significantly increases the adsorptive capacity of GAC for five of these six compounds. The oxic GAC adsorptive capacity for o-cresol, for example, can be up to 2.6-fold the capacity that is attainable under anoxic conditions. Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(81 citation statements)
references
References 11 publications
10
70
1
Order By: Relevance
“…Singlesolute isotherms for each of the compounds were obtained using the Freundlich equation; q = kc l/n (Abuzaid and Nakhla 1994;Abuzaid et al 1995). Our results for o-cresol and 4-nitrophenol also indicate that oxygen enhances their adsorption, which is what other research groups also found (Vidic and Suidan 1991).…”
Section: Resultssupporting
confidence: 90%
“…Singlesolute isotherms for each of the compounds were obtained using the Freundlich equation; q = kc l/n (Abuzaid and Nakhla 1994;Abuzaid et al 1995). Our results for o-cresol and 4-nitrophenol also indicate that oxygen enhances their adsorption, which is what other research groups also found (Vidic and Suidan 1991).…”
Section: Resultssupporting
confidence: 90%
“…Activation process of the ALPC by immersing it in a strong acid (HCl) might change the clay mineral's structure, and created more heterogeneous adsorption sites and increased its specific surface [33]. The kF values obtained from NOM adsorption onto the LCP and the ALCP were 12.6 and 14.91, respectively, while if compared with other studies, which using nanomaterials and carbon materials as adsorbents, their kF values obtained were in a range of 100-200 [34], [35]. This means that the adsorption capacity values yielded by the LCP and ALCP were smaller than other materials.…”
Section: Nom Adsorption Isothermsmentioning
confidence: 84%
“…Physical adsorption processes dominate at short equilibration times, low temperatures, low pH, and low concentrations of molecular oxygen. In contrast, oxidative coupling, a polymerization reaction catalyzed by carbon surfaces in which phenol multimers are formed through C-O and C-C linkages, becomes important under opposite conditions in each of the above respects [8][9][10].…”
Section: Introductionmentioning
confidence: 99%